قياس الجراة الاجتماعية لدى طلبة الجامعة (Journal Of Educational and Psychological Researches, 2015)
The current research was aimed at the following:1. Measurement of   Boldness among the students of  university. Identify the differences in Boldness between university students according to variable of Sex (male / female) and variable of Specialization (scientific / literary).To achieve this aims of the research, the researcher set up the instrument is scale of the Boldness that consistent (34) item, and the researcher applying this scale on the sample amounted to (200) student of  University. Then   after data processing statistically, the researcher reached the following results: The students of university have Boldness. There is difference in Boldness between university students according to variable of Sex (male / female) benefit for female, and there is difference in Boldness between university students according to variable of Specialization (scientific / literary) benefit for literary. In light of the results of this research the researcher came out with a number of recommendations and suggestions